Updated Survival Data for a Phase I/II Study of Carboplatin plus Nab‐Paclitaxel and Concurrent Radiotherapy in Patients with Locally Advanced Non‐Small Cell Lung Cancer. (24th October 2019) - Tsuchiya‐Kawano, Yuko; Sasaki, Tomonari; Yamaguchi, Hiroyuki; Hirano, Katsuya; Horiike, Atsushi; Satouchi, Miyako; Hosokawa, Shinobu; Morinaga, Ryotaro; Komiya, Kazutoshi; Inoue, Koji; Fujita, Yuka; Toyozawa, Ryo; et al.
Abstract: Lessons Learned: Updated survival data for a phase I/II study of carboplatin plus nab ‐paclitaxel and concurrent radiotherapy were collected. In the group of 58 patients who were enrolled at 14 institutions in Japan, the median overall survival was not reached and the 2‐year overall survival rate was 66.1% (95% confidence interval, 52.1%–76.8%). Results reveal encouraging feasibility and activity for this regimen. Background: We report the updated survival data for a phase I/II study of carboplatin plus nab ‐paclitaxel ( nab ‐P/C) and concurrent radiotherapy (CRT) in patients with locally advanced non‐small cell lung cancer (NSCLC). Methods: Individuals between 20 and 74 years of age with unresectable NSCLC of stage IIIA or IIIB and a performance status of 0 or 1 were eligible for the study. Patients received weekly nab‐paclitaxel at 50 mg/m 2 for 6 weeks together with weekly carboplatin at an area under the curve (AUC) of 2 mg/ml/min and concurrent radiotherapy with 60 Gy in 30 fractions. This concurrent phase was followed by a consolidation phase consisting of two 3‐week cycles of nab‐paclitaxel (100 mg/m 2 on days 1, 8, and 15) plus carboplatin (AUC of 6 on day 1). After the treatment, patients were observed off therapy. The primary endpoint of the phase II part of the study was progression‐free survival (PFS). Results: Between October 2014 and November 2016, 58 patients were enrolled at 14 institutions in Japan, with 56 of these individuals being evaluable for treatment efficacy and safety. At the median follow‐up time of 26.0 months (range, 4.0–49.6 months), the median overall survival (OS) was not reached (95% confidence interval [CI], 25.3 months to not reached) and the 2‐year OS rate was 66.1% (95% CI, 52.1%–76.8%). The median PFS was 11.8 months (95% CI, 8.2–21.0 months), and the 2‐year PFS rate was 35.9% (95% CI, 23.1%–48.9%). Subgroup analysis according to tumor histology or patient age revealed no differences in median PFS or OS. Long‐term follow‐up of toxicities did not identify new safety signals, and no treatment‐related deaths occurred during the study period. Conclusion: Concurrent chemoradiation with nab‐P/C was safe and provided a long‐term survival benefit for patients with locally advanced NSCLC.